Pension Provision in Thailand - Palacios, Robert (World Bank, Washington, DC, 2021)
This report documents the current state of pension provision in Thailand and options for reform that would increase the adequacy and sustainability of the pension system. While the focus here is on income support, the welfare of the elderly depends on many other government policies ranging from labor market policies to aged care and health services. It is also important to assess the pension system in terms of its broader impact on fiscal sustainability and national savings. This analysis can be found in a companion World Bank report that looks at the macroeconomic implications of aging in Thailand. The next section describes the schemes for the formal sector (public and private sector) followed by sections two and three which cover voluntary programs for the informal sector and non-contributory or ‘social’ pensions, respectively. Section four assesses performance based on three criteria, adequacy, sustainability, and coverage. The last section concludes.